Rere Atu Taku Poi: The Artform That Allows for True Identity and Expression - Paora, Tangaroa; Mortensen Steagall, Marcos (Translator) (School of Art and Design, AUT, 2024)
Over the past 30 years, poi has been a significant tool in Kapa Haka (Māori performing arts) where women have used the poi to demostrate beauty, grace and femininity. However, poi and its influence on the artform has made its way back into the world of Kapa Haka recognising the divine creativity that Māori men bring to this aspect of performance. Despite very few male’s performing poi on competitive stages such as Ngā Kapa Haka Tuarua o Aotearoa (Secondary National competition) or Te Matatini (Senior Kapa Haka National competition), we are seeing more male’s perform poi in general. This now traces back to the origin point of poi being used traditionally by men as a training tool to prepare for combat to now being in contemporary times, where it is used to express ones authentic self. Tāne Māori who are recognised as poi experts identify or connect with the idea of being takatāpui. This article discusses the journey of reclamation of an artform that originates itself in the notion of the masculinity to now being revolutionised to the expression of femininity and in turn creates the idea of irarere an artform that merges both the masculine and feminine being through expression of poi. For some, poi can be a space to freely show who you are, connected to through cultural expression and affirming in idenitiy. It is through poi performance that takatāpui are able to perform in such a way that blurs this binary idea of male and female, of masculine and feminine, of gender and sexuality, of performing and being. This allows for the exploration of the unknown and gives way to those who choose to forge a new path in performative expression. Carrying on from Paora (2023) doctoral study on the artistic reconsideraiton of gender role differentiation that gives voice to takatāpui identity, this discussion seeks to affirm that poi as a traditional training tool or contemporary artform is the space for takatāpui to explore themselves and how they express their true authentic being.